The profession of professional football player: a feasible reality or a distant dream for young brazilian teenagers? (Research, Society and Development, 2022)
Adolescence is a fundamental stage in the human development process and soccer is one of the great cultural phenomena. Based on the perception of the existence of a significant relationship between adolescence and soccer, a qualitative-descriptive study was developed from a bibliographic research, which used as reference material the doctoral thesis of Rottmann, defended in 2019 in the Graduate Program in Education at UNILASALLE. From the data extracted from this thesis, it sought to understand the meaning of soccer in the imaginary of adolescents and its possible interference in their ways of living, in addition to trying to unravel whether becoming a player in this sport would refer to a reality possible for any talented youngster or if this phenomenon would refer to a distant dream, available only to a small number of young people. The extracted data pointed out that the reasons for the presence of soccer-related representations in the adolescents' imagination seem to be linked to the exuberant space that soccer occupies in the contemporary media, making young people ignore the obstacles inherent to the possibility of becoming a player, such as emotional control, posture, luck, good technical level, possible injuries, insane competition, among others. Thus, the study points out that the possibility of a young person, in Brazil, becoming a player would be much more linked to a distant dream than to a reality possible to be reached by any young person who shows talent and willingness to achieve this goal.